Disability-Friendly Flats with Ecology Architecture Approach - Cyndi Natalia Hutabarat; Nelson M Siahaan (International Journal of Architecture and Urbanism, 2022)
A disability-friendly flat is a vertical residence that can be accessed and used by everyone including persons with disabilities and the elderly. The implementation of access in vertical buildings that are friendly to people with disabilities has not become a particular concern, especially in Indonesia. Hence, they still experience difficulties and obstacles in carrying out their activities. Disability-friendly flats located in an urban area and close to various public facilities aim to accommodate the problem of the high demand for housing in urban communities, overcome the problem of limited land and green space, provide easy access and achievement, and also realize the life of disability users that is more qualified, fair, physically and mentally prosperous, independent, and dignified. This flat was designed by using an Ecological Architecture approach to decrease environmental issues and problems in an urban area, also create comfort and independence for disability users through the application of these ecological principles that applied to building zones, materials, vegetation, and rainwater that can stimulate the human senses to recognize or identified place. The research method uses descriptive qualitative methods and data collection is obtained through field surveys, comparative studies, and literature studies. The design of this flat considered the vertical access inside the building by providing facilities such as stairs, ramps, and lifts to make it easier for all flat users, including persons with disabilities and the elderly